Diagnostic procedures in hepatobiliary surgery - Delgado, Bolívar; Gaudiano, Javier; Muxi, Fernando; Petersen, Federico; Sálice, Mario; Bermúdez, Jorge; Collazo, José M; Perrier, José P; Piñeyro, Alberto; Piñeyro, Luis; Sojo, Enrique (Cirugía del Uruguay, 1981)
This Panel Meeting analyzed sone of the procedures employed in diagnosis of Hepatobiliary Surgery with particular reference to 2 situations: jaundice and nodular liver.